2018
DOI: 10.1242/jcs.214536
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome stress leads to APP axonal transport defects by promoting its amyloidogenic processing in lysosomes

Abstract: Alzheimer disease (AD) pathology includes the accumulation of poly-ubiquitylated (also known as poly-ubiquitinated) proteins and failures in proteasome-dependent degradation. Whereas the distribution of proteasomes and its role in synaptic function have been studied, whether proteasome activity regulates the axonal transport and metabolism of the amyloid precursor protein (APP), remains elusive. By using live imaging in primary hippocampal neurons, we showed that proteasome inhibition rapidly and severely impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 88 publications
(126 reference statements)
3
7
0
Order By: Relevance
“…Our work fits perfectly with the journal scope, and our previous work that described the axonal transport properties of the proteasome complex for the first time was published in Journal of Cell Science (Otero et al, 2014). We thought it would be an excellent opportunity to complete the story with this newly discovered role of the proteasome complex in axonal transport regulation of APP.…”
Section: Why Did You Choose Journal Of Cell Science For Your Paper?supporting
confidence: 78%
“…Our work fits perfectly with the journal scope, and our previous work that described the axonal transport properties of the proteasome complex for the first time was published in Journal of Cell Science (Otero et al, 2014). We thought it would be an excellent opportunity to complete the story with this newly discovered role of the proteasome complex in axonal transport regulation of APP.…”
Section: Why Did You Choose Journal Of Cell Science For Your Paper?supporting
confidence: 78%
“…Furthermore, the ubiquitin‐proteasome system, another mechanism degrading misfolded proteins, is abnormally modulated in individuals with obesity resulting in the aggregation of macromolecules in different tissues . Both defective autophagy and proteasome dysfunction in adipose tissue, liver, pancreas, and neurons have been proposed to cause T2DM and Alzheimer disease (AD) . Although protein aggregates accumulate gradually with age, the obesity‐induced accumulation of damaged proteins, and obesity‐inhibited autophagy and ubiquitin proteasome system may speed up the cellular senescence and premature apoptosis due to dysregulated protein homeostasis.…”
Section: Obesity Reinforces Machinery Of Ageingmentioning
confidence: 99%
“…Recently, live-cell imaging in hippocampal neurons revealed that proteasomal inhibition impairs the axonal transport of APP by stimulating its trafficking to the endo-lysosomal system for cleavage. This study underlines the importance of proteasome-lysosome crosstalk and implicated proteasomal dysfunction in the abnormal APP metabolism causing axonal degeneration in some neurodegenerative diseases [302].…”
Section: Proteasome-other Organellesmentioning
confidence: 58%